Tanzania Economic Update, July 2019 : Human Capital - The Real Wealth of Nations - World Bank Group (World Bank, Washington, DC, 2019)
Investing in human capital is essential for Tanzania. To generate future income and achieve sustainable development, people are the most important asset countries have. Part two of this economic update discusses where Tanzania stands in terms of its investments in human capital for both children and adults. The analysis is part of the World Bank Human Capital Project (HCP), which relies on both the Human Capital Index (HCI) and data on human capital wealth (HCW).